Disseminated histoplasmosis in a patient with rheumatoid arthritis and interstitial lung disease - Deepak Rosha; Ishan Gupta; Vijay Kiran Gandham; Piyush Goyal (Apollo Medicine)
Histoplasmosis is a rare systemic fungal ailment. The clinical presentation of this disease is nonspecific and most physicians lack awareness about this disease. There is a paucity of diagnostic tests, due to which fungal infections remain undiagnosed. The dissemination of this infection beyond the lungs can remain asymptomatic. Infection mostly heals on its own but in few cases, it manifests as a pulmonary disease, very similar to tuberculosis. Systemic spread occurs in patients with debilitating diseases and those who are immunocompromised. We report a rare case of disseminated histoplasmosis in a 54-year-old female suffering from rheumatoid arthritis with interstitial lung disease with lung and bone marrow involvement. Appropriate administration of antifungal agents led to remarkable improvement.